Particle bombardment and subcellular protein localization analysis in the aquatic plant Egeria densa - Yasuhide Osaki; Yutaka Kodama (PeerJ, 2017)
Particle bombardment is a powerful and relatively easy method for transient expression of genes of interest in plant cells, especially those that are recalcitrant to other transformation methods. This method has facilitated numerous analyses of subcellular localization of fluorescent fusion protein constructs. Particle bombardment delivers genes to the first layer of plant tissue. In leaves of higher plants, epidermal cells are the first cell layer. Many studies have used the epidermal cell layer of onion bulb (Allium cepa) as the experimental tissue, because these cells are relatively large. However, onion epidermal cells lack developed plastids (i.e., chloroplasts), thereby precluding subcellular localization analysis of chloroplastic proteins. In this study, we developed a protocol for particle bombardment of the aquatic plant Egeria densa, and showed that it is a useful system for subcellular localization analysis of higher plant proteins. E. densa leaflets contain only two cell layers, and cells in the adaxial layer are sufficiently large for observation. The cells in both layers contain well-developed chloroplasts. We fused fluorescent proteins to conventional plant localization signals for the nucleus, cytosol, mitochondria, peroxisome, and chloroplast, and used particle bombardment to transiently express these fusion constructs in E. densa leaves. The plant subcellular localization signals functioned normally and displayed the expected distributions in transiently transformed E. densa cells, and even chloroplastic structures could be clearly visualized.